#FYP untuk UMKM: Strategi Digital Marketing TikTok dalam Penguatan Brand dan Konversi Usaha Kost - Wiryawan, I Gusti Ngurah Dwi; Sosianika, Adila; Aprianissa, Syifa Nur; Lisoni, Kaniya; Abdurrauf, Husni Muhammad (Penerbit Widina, Widina Media Utama, 2025)
This community service activity aims to empower MSMEs in the housing services sector, specifically women's boarding houses, through mentoring in digital marketing strategies using TikTok as a social media platform. The targeted partner was a boarding house owner in Sarijadi, Bandung, who had not previously implemented any digital promotion strategy. The program was conducted from February to May 2025, involving one business partner and seven students from the Business Administration Study Program. The implementation method used a participatory approach, consisting of three stages: (1) identifying partner conditions through observation and interviews; (2) designing a digital marketing strategy, including the creation of visual identity, opening a TikTok account, and developing a content calendar; and (3) executing the campaign and evaluating its performance using TikTok Analytics. The results showed positive achievements: 384 new followers, 400,000 video views, increased digital engagement, and four previously vacant rooms successfully rented during the campaign. The partner also demonstrated improved understanding of digital promotion strategies and the ability to manage social media independently. The program was well received by the partner and surrounding community. The increase in digital literacy and promotional independence strengthened the business's competitiveness in the digital era. The short-video content strategy proved effective and applicable for MSMEs without requiring large budgets, while also serving as a practical learning experience for students and a tangible contribution from the university in supporting MSME digital transformation.ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk memberdayakan pelaku UMKM di sektor jasa hunian, khususnya kost perempuan, melalui pendampingan strategi digital marketing berbasis media sosial TikTok. Mitra sasaran adalah pemilik kost di Sarijadi, Kota Bandung, yang belum memiliki strategi promosi digital. Kegiatan dilaksanakan pada Februari–Mei 2025, melibatkan satu mitra usaha dan tujuh mahasiswa dari Program Studi Administrasi Niaga. Metode pelaksanaan menggunakan pendekatan partisipatif dengan tiga tahapan: (1) identifikasi kondisi mitra melalui observasi dan wawancara; (2) perancangan strategi digital, meliputi pembuatan identitas visual, pembukaan akun TikTok, serta penyusunan kalender konten; dan (3) implementasi kampanye serta evaluasi performa melalui TikTok Analytics. Hasil menunjukkan capaian positif: 384 pengikut baru, 400.000 tayangan video, peningkatan interaksi digital, dan empat kamar kost yang sebelumnya kosong berhasil disewa. Mitra juga mengalami peningkatan pemahaman terhadap strategi promosi dan mampu mengelola media sosial secara mandiri. Kegiatan ini diterima dengan baik oleh mitra dan lingkungan sekitar. Peningkatan literasi digital dan kemandirian promosi memperkuat posisi usaha di era digital. Strategi konten video pendek terbukti efektif dan aplikatif bagi UMKM tanpa anggaran besar, serta menjadi sarana pembelajaran praktis bagi mahasiswa dan kontribusi nyata perguruan tinggi dalam mendorong transformasi digital UMKM.